Psychological balance in high level athletes: Gender-based differences and sport-specific patterns - Schaal, K.; Tafflet, M.; Nassif, H.; Thibault, V.; Pichard, C.; Alcotte, M.; Guillet, T.; El Helou, N.; Berthelot, G.; Simon, S.; Toussaint, J.-F. (PLOS ONE, 2011)
Objectives: Few epidemiological studies have focused on the psychological health of high level athletes. This study aimed to identify the principal psychological problems encountered within French high level athletes, and the variations in their prevalence based on sex and the sport practiced.